Advertising of ultra-processed foods and beverages: children as a vulnerable population - Christina Mallarino; Luis F Gómez; Laura González-Zapata; Yazmín Cadena; Diana C Parra (Universidade de São Paulo, 2013)
The rapid nutrition transition occurring in Latin America has resulted in a sharp increase of childhood overweight and obesity. Recent evidence has shown that food and beverage advertising has a great influence on children's eating behavior. This population has become a key target market for the ultra-processed foods and beverages industry, which is marketing products in an aggressive way. Evidence shows that Latin American countries have poor regulation of ultra-processed foods and beverages advertising, where the discourse of self-regulation still prevails over statutory regulations. The following commentary explores how advertising might play an important role in developing unhealthy dietary patterns and obesity in Latin American children, as well as the urgent need for government action and the involvement of civil society to tackle this public health issue.